Pengaruh Pengaruh Pendidikan Kewirausahaan dan Penggunaan E-Commerce terhadap Minat Berwirausaha Digital pada Siswa SMKN 6 Surakarta - Pringgosari, Antonia Nataya; Susilangingsih, Susilaningsih (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2025)
This study aims to find empirical evidence (1) the influence of entrepreneurship education on digital entrepreneurship interest in students of SMK Negeri 6 Surakarta; (2) the influence of e-commerce use on digital entrepreneurship interest in students of SMK Negeri 6 Surakarta; and (3) the influence of entrepreneurship education and e-commerce use on digital entrepreneurship interest in students of SMK Negeri 6 Surakarta. This study is a study using a descriptive quantitative method. The population in this study were students of SMK Negeri 6 Surakarta with a purposive sampling technique resulting in a sample of 106 respondents. Data collection was carried out by distributing questionnaires to respondents and in the form of documentation to find out the curriculum and learning process implemented. The instrument validity test technique used Karl Person's product moment correlation and the instrument reliability test was carried out using the Alpha Cronbach technique. Data analysis in this study used multiple linear regression analysis techniques. The results of this study are as follows (1) there is an influence of entrepreneurship education on digital entrepreneurship interest; (2) the use of e-commerce has an impact on interest in digital entrepreneurship; (3) entrepreneurship education and the use of e-commerce contribute 60% to interest in digital entrepreneurship. The researcher hopes that other researchers can develop research based on the facts in the background, namely the low execution of becoming an entrepreneur even though the interest in becoming an entrepreneur is quite high.